Reproductive modes and fecundity of an assemblage of anuran amphibians in the Atlantic rainforest, Brazil - Hartmann, Marilia T.; Hartmann, Paulo A.; Haddad, Celio Fernando Baptista [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2010)
Neste estudo são apresentados os modos reprodutivos e as relações de tamanho-fecundidade dos anuros encontrados em Picinguaba, uma região de Mata Atlântica no litoral norte do estado de São Paulo. Foram registrados 13 modos reprodutivos, confirmando a alta diversidade de modos reprodutivos encontrados na Mata Atlântica. A diversidade de modos reprodutivos observados na Mata Atlântica é o resultado do sucesso dos anuros na utilização dos diversos microhábitats úmidos desse bioma. Os comprimentos rostro-cloacais de 715 indivíduos de 40 espécies de anuros foram medidos. Foram consideradas as relações de tamanho-fecundidade para 12 espécies. O tamanho do corpo explicou entre 57% e 81% da variação no tamanho da ninhada. Os modos reprodutivos aquáticos apresentaram maior número de ovos, comparados aos modos reprodutivos terrestres ou arborícolas. As espécies com maior tamanho de ovos foram as que apresentaram modos reprodutivos especializados.

Reproductive modes and size-fecundity relationships are described for anurans from Picinguaba, a region of Atlantic rainforest on the northern coast of the state of São Paulo, Brazil. We observed 13 reproductive modes, confirming a high diversity of modes in the Atlantic rainforest. This diversity of reproductive modes reflects the successful use of diversified and humid microhabitats by anurans in this biome. We measured the snout-vent length of 715 specimens of 40 species of anurans. The size-fecundity relationship of 12 species was analyzed. Female snout-vent lengths explained between 57% and 81% of clutch size variation. Anurans with aquatic modes laid more eggs than those with terrestrial or arboreal modes. Larger eggs were deposited by species with specialized reproductive modes.
Modos reprodutivos e fecundidade de anfíbios anuros em uma taxocenose na Mata Atlântica, Brasil
Keywords: Reprodução; Anura; tamanho da ninhada; comunidade; Reproduction; Anura; clutch size; community